2021
DOI: 10.1097/md.0000000000024199
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture therapy strategy options in postoperative management after laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy (LC) is a common surgery accompanied by some unpleasant adverse effects. Clinical trials indicated that acupuncture therapy may help reduce complications in LC. However, no systematic reviews have been conducted on the topic. Therefore, we will evaluate the current evidence and provide a rank for the efficacy of acupuncture therapy in LC by performing Bayesian network meta-analysis. Methods: A total of 9 database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The main finding of the current meta-analysis was the analgesic efficacy of acupuncture as demonstrated by a higher percentage of participants achieving effective pain relief and a reduced ESWL-related pain severity compared to those in the control groups. Consistent with our findings, other systematic reviews have supported the promising outcomes of conventional acupuncture and related methods (e.g., auricular acupuncture, electroacupuncture, or acupoint electrical stimulation) in postoperative pain management (52) among patients undergoing back surgery (53), cardiac surgery (54), total knee replacement (55), and laparoscopic surgery (56). Therefore, our results suggested that acupuncture may be an effective analgesic strategy for patients receiving ESWL.…”
Section: Discussionsupporting
confidence: 90%
“…The main finding of the current meta-analysis was the analgesic efficacy of acupuncture as demonstrated by a higher percentage of participants achieving effective pain relief and a reduced ESWL-related pain severity compared to those in the control groups. Consistent with our findings, other systematic reviews have supported the promising outcomes of conventional acupuncture and related methods (e.g., auricular acupuncture, electroacupuncture, or acupoint electrical stimulation) in postoperative pain management (52) among patients undergoing back surgery (53), cardiac surgery (54), total knee replacement (55), and laparoscopic surgery (56). Therefore, our results suggested that acupuncture may be an effective analgesic strategy for patients receiving ESWL.…”
Section: Discussionsupporting
confidence: 90%